The Role of The Village Government in The Empowerment And Development of Art Tourism Villages in Gegesik Kulon Village, Gegesik District, Cirebon Regency - Riyani, Ade; Hidayat, Rochmat; Wildanu, Eka (ann4publisher@gmail.com, 2024)
The method used in this study is a descriptive method with a qualitative approach. The data collection technique uses observation, interview, and documentation techniques. The informant selection technique in this study uses a purposive sampling technique. This study uses two research focuses; the first is the role of village government in empowerment, according to Jim Ife and Frank Tesoriero, namely social animation, mediation and negotiation, group facilitation, provision of support, utilization of resources and skills, and organizing. Nuryanti prioritized two developments in the tourist village, namely, attractions, accommodation, and supporting facilities. The study results are the village government's role in empowerment. First, social animation has been running well, although there is a lack of motivation and inspiration indicators. Second, mediation and negotiations have gone well, although the program socialization indicators have found obstacles to overcome. Thirdly, the support providers are pretty good, but there are shortcomings in funding indicators. Fourth, the facilitation of the group is quite good but not optimal and needs to be improved by the village government. Fifth, using resources and skills is quite good, but the implementation is still not optimal. Sixth, the organization is going well but must continue to be improved to maximize it. As for the development of tourist villages, first, tourist attractions are running well but are still not optimal. Secondly, the accommodation is quite reasonable, but there are still shortcomings. The three supporting facilities are pretty good but still need a lot of improvements.